2021
DOI: 10.1111/jpr.12368
|View full text |Cite
|
Sign up to set email alerts
|

Development of a 3‐Day Intervention Program for Family Members of Hikikomori Sufferers1

Abstract: Revision of the ProgramWe modified the contents of a 1-day (and a 5-day) program to a 3-day program, which consisted of three sessions (180 min per session), as follows:1. We introduced the "small-step approach." We presumed a variety of parent-child

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 15 publications
0
16
0
Order By: Relevance
“…Furthermore, studies have indicated that deteriorating family relationships may intensify the mental health problems caused by COVID-19 (Stavridou et al, 2020). Thus, family support is expected to prevent mental health problems and transition to hikikomori (Kubo et al, 2020(Kubo et al, , 2021.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, studies have indicated that deteriorating family relationships may intensify the mental health problems caused by COVID-19 (Stavridou et al, 2020). Thus, family support is expected to prevent mental health problems and transition to hikikomori (Kubo et al, 2020(Kubo et al, , 2021.…”
Section: Discussionmentioning
confidence: 99%
“…(1) living with hikikomori sufferers (2) participant receiving standard hikikomori family support (treat as usual; TAU) (3) age 20 years or older (4) hikikomori duration of their hikikomori sufferer was at least 6 months. The exclusion criteria were as follows; (1) participants have learned MHFA program previously, (2) hikikomori sufferers had continuously used the support institutions within the past 6 months, (3) difficulty in reading or writing Japanese, (4) difficulty in attending the program continuously due to a serious physical or psychiatric symptoms, (5) daily violence from the hikikomori sufferers, (6) the intervention is likely to cause danger to the participants or their family due to severe aggression of hikikomori sufferers, (7) the intervention is likely to cause hikikomori sufferers' suicidal ideation or self-harming behavior.…”
Section: Participantsmentioning
confidence: 99%
“…The Hikikomori Behavior Checklist (HBCL) was used to assess the problematic behaviors of hikikomori sufferers (17). This scale is consisted of 45 items and has 10 factors as subscales: (1) Aggressive behavior (eight items), (2) Social anxiety (four items), (3) Obsessive-compulsive behavior (four items), (4) Avoidance from family members (five items), ( 5) Depression (four items), ( 6) Absence of activities of daily living (six items), (7) Incomprehensible maladapted behavior (five items), ( 8) Absence of social participation (three items), (9) Decreased activity (three items), and (10) Irregular life pattern (three items). Respondents were asked regarding behavior within the last 3 months with a 4-point scale from 0 (not at all) to 3 (strongly agree).…”
Section: Problematic Behaviors Of Hikikomori Sufferersmentioning
confidence: 99%
“…Accordingly, one could argue that a trans-cultural adaptation of Hikikomori interventions are still highly needed, taking into account the abovementioned cultural and societal variations in the Western context. At this regard, Kubo et al (2020); Kubo, Urata, et al (2021) has recently proposed a 5-day full programme and 3-day intensive family-based intervention for family members of Hikikomori subjects by the research team coordinated by Kato (Kubo et al, 2020); (Kubo, Urata, et al 2021). However, although our research team has cross-culturally adapted the abovementioned culturally-bound Japanese interventions into the Italian context and is recruiting a sample for a cross-cultural validation process, further studies should be implemented in the treatment as well as diagnostic directions, being Hikikomori currently a worldwide reality.…”
Section: Towards a Culture-based Hikikomori Definition And Therapy?mentioning
confidence: 99%
“…Hikikomori subjects are extremely difficult to engage and convince in accepting a preliminary psychiatric consultation (including an interview and an assessment to confirm the condition) and this results in a delay of about 4.4 in asking for therapeutic help which may involve both the individual and family system (Kondo et al, 2010). For this reason, some authors suggested implementing interventions to engage family members and caregivers of Hikikomori individuals to indirectly convince them to ask mental health professional support, such as the recently adapted intervention comprising Mental Health First Aid (MHFA) and the educational programme based on cognitive-behavioural approach of the Community Reinforcement and Family Training (CRAFT) as well as a tailored psychotherapy approach (Imai et al, 2020; Kato, Kanba & Teo, 2019; Kubo et al, 2020; Kubo, Urata, et al, 2021; Meyers et al, 1998; K. Saito, 2010; Sakai et al, 2015; J.…”
Section: Towards a Culture-based Hikikomori Definition And Therapy?mentioning
confidence: 99%